Analisis Faktor Yang Berhubungan Dengan Tingkat Stres Pada Ibu Hamil Dalam Menghadapi Persalinan - Manuntungi, Andi Ernawati; Rabuana, Susi; D, Yuliana; Suaib, Suaib (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
Stress in pregnant women is related to causing stress during pregnancy, childbirth and postpartum. The aim of this research is to look at factors related to stress levels in pregnant women when facing childbirth. This type of research is an analytical survey with a cross sectional approach carried out in the Tobadak Health Center Work Area. The population is all pregnant women who visit the Tobadak Community Health Center Working Area using accidental sampling technique. Data was collected using a questionnaire with the results of the validity analysis value r>0.267 and the reliability test having a Cronbach's Alpha value>0.7 and processed manually, using univariate and bivariate analysis with the chi-square test. The research results showed that there was a relationship between family support and stress levels, there was a relationship between husband's support and stress levels, there was a relationship between traumatic experiences and stress levels, there was a relationship between personal preparedness levels and stress levels and there was a relationship between activity levels and stress levels.